On poetic emotiology in poetry and beyond - Sinelnikova, Lara N.; Selezneva, Larisa V. (Slovo.ru : Baltiĭskiĭ akt͡s︡ent, 2021)
The article presents material supporting the thesis about the discourse register of emotions in their movement from poetic communications to non-poetic ones. The subjects of the description are emotives — linguistic signs of emotions. The part of the article that deals with poetry interprets emotives in multiple aspects: in the aspect of the grammar of poetic language and in their figurative representation. Within the frames of such grammatical categories as the imperative and subjunctive moods, emotives acquire typologically significant cognitive and semantic characteristics: a drive to display emotions, desire and the unattainability of the desired. The semantic features of emotives are revealed in the structures of the 'inner speech': in interrogative structures and pseudo-dialogical reflexions. The figurative representation of emotions is realised through conceptual metaphors, which bestow upon emotions new characteristics correlating to personal mental images of the emotional world. The linguistic means of representing emotions are closely linked to the features of the social period, to existential demands and to the state of public consciousness. The part of the article that is related to non-poetic communication interprets such links based on the examples of PR and advertising discourses. The particular "poetic" use of language is, of course, most obvious in poetry, but a broad understanding of the poetic function allows us to speak of the "poetic in the non-poetic". In the segment of the article related to non-poetical communication, linguistic representations of emotions and techniques for creating "referential illusions" are considered on the example of PR-discourse and advertising discourse. Attention is focused on discursive transformations associated with the formation of a mythological world in which its own special laws operate. In both discourse types, orientation towards results correlates with orientation towards the message itself.